Elderly Mistreatment: Risk Factors and Therapy - Madina, Ummi Ulfah; Dwimartutie, Noto (UI Scholars Hub, 2016)
Elderly mistreatment is a preventable serious health problem that lowering older adults quality of life. Elderly mistreatment can be done by the caregiver or even the patient himself, regardless the intention. Meanwhile, defining an elderly mistreatment is still a challenge due to varied risk factors and cultural differences in each country. Those conditions result in challenges in identifying and managing elderly mistreatment. This review will also discuss screening modalities to identify elderly who is at risk or currently abused to prevent and manage elderly mistreatment properly.